Associations of adverse childhood experiences with common psychiatric disorder in later life: results from the China mental health survey - Jinhao Li; Zhaorui Liu; Minghui Li; Yueqin Huang; Huifang Yin; Guangming Xu; Lingjiang Li; Tingting Zhang; Jie Yan; Yaqin Yu; Xiufeng Xu; Zhizhong Wang; et al. (BMC Geriatrics, 2023)
Abstract Background Associations between adverse childhood experiences (ACEs) and common psychiatric disorders among older Chinese individuals have not been well reported. The objectives of this study are to examine the prevalence of ACEs and the associations of ACEs with common psychiatric disorders among older adults in China. Methods The study used data from the China Mental Health Survey (CMHS), a nationally representative epidemiological survey, which used computer-assisted personal interviewing (CAPI), logistic regression models were used to examine community-based adult psychiatric disorders and associated risk factors. Finally, 2,317 individuals aged 60 years or over were included in the CMHS. The national prevalence of ACEs in older adults were estimated and logistic regression were used to analyse the association between ACEs and past-year psychiatric disorders. Results Prevalence of ACEs among older adults in China was 18.1%. The three most common types of ACEs were neglect (11.6%), domestic violence (9.2%), and parental loss (9.1%). This study proved the association between ACEs and common past-year psychiatric disorders in older adults. ACEs increased the risk of past-year psychiatric disorders in older adults. After adjustment for age, sex, marital status, employment status, education, rural or urban residence, region, and physical diseases, the association between ACEs and past-year psychiatric disorders were still significant. Conclusions ACEs are linked to an increased risk for past-year psychiatric disorders in older adults. ACEs may have long-term effects on older adults’ mental well-being. Preventing ACEs may help reduce possible adverse health outcomes in later life.